2016
DOI: 10.21161/mjm.71215
|View full text |Cite
|
Sign up to set email alerts
|

Citric acid production by Aspergillus niger using different substrates

Abstract: Aims: Citric acid is a commercially important acid that has many applications in varying sectors of industries. It is produced by various substrates through solid state or submerged fermentation. The capabilities of potato and rice as substrates for citric acid production using Aspergillus niger were tested in this experiment under submerged fermentation. Methodology and results: Potato and rice extract media were prepared and inoculated with A. niger and titrations were carried out to determine the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Lee et al [5] found sucrose to be an important carbon source in submerged fermentation with citric acid measured at pH 2. Similar findings were also reported by Chirova et al [13]. It is also important to note that the cell growth and consequent metabolic activity of a pelleted suspension occur mainly at the culture medium surface where there is access to adequate oxygen and nutrients [12].…”
Section: Isolation Of Citric Acid-producing Aspergillus Niger From Sosupporting
confidence: 85%
“…Lee et al [5] found sucrose to be an important carbon source in submerged fermentation with citric acid measured at pH 2. Similar findings were also reported by Chirova et al [13]. It is also important to note that the cell growth and consequent metabolic activity of a pelleted suspension occur mainly at the culture medium surface where there is access to adequate oxygen and nutrients [12].…”
Section: Isolation Of Citric Acid-producing Aspergillus Niger From Sosupporting
confidence: 85%
“…Citric acid production with potato extract media supplemented with different and varying concentration increased as the potato extract and its supplement increased" [15]. Kudzai et al [16] reported "potato and rice starch extract during citric acid production by Aspergillus niger and found that different substrates have different effects on biosynthesis of citric acid depending on their concentrations. These suggested that carbon source and its concentration had a great influence on citric acid production depending on the nature and type carbon used for fermentation".…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the researcher and industries look for the raw materials that could reduce citric acid productions cost. Some study conducted for use some agriculture production to become citric acid as a raw material [2]. Nowadays in Thailand, rice is the major locally produced crop, which amounted to 20.7 million metric tons in 2019 [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, rice certainly has the opportunity to be an ingredient to produce citric acid. The ability of rice and potato as an extract to produce citric acid was analyzed by Kudzai et al [2] in order to meet the high demand for citric acid. The result was shown that rice could provide the highest production of citric acid, and rice extract media proved to be more useful than potato extract media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation